Gambaran kejadian pulpitis di wilayah kerja Puskesmas Dawan I Klungkung - I Gede Krisna Merta Yoga; Putu Ratna Kusumadewi Giri; Ketut Suarjana (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: Dental caries is a multifactorial disease in hard tissue that can occur when there are factors interrelated to one another. Untreated dental caries will reach the pulp and cause pulp inflammation or pulpitis. Factors that cause pulpitis are internal factors and external factors. Aim: The purpose of this study is to know the prevalence of pulpitis in the region of Dawan I primary health center.Methods: Descriptive study used with cross sectional study approach was used in this study. Sample of 107 people was obtained by simple random sampling. Results: The result showed that prevalence of pulpitis in the region of Dawan I primary health center is high (25.2%). Meanwhile, the prevalence of respondents who have bad habit amounted to 66.7%. Respondents who have bad healthy behavior amounted 85.2%. Association between pulpitis and habit are significant in statistics (p=<0.001). The prevalence of pulpitis more occur in bad nutrition intake amounted 100%. Association between pulpitis and nutrition are significant in statistics (p=<0.001). Conclusions: It is concluded that the prevalence of pulpitis in the region of Dawan I primary health center is high. Community in the region of Dawan I primary health center which mostly pulpitis have a bad habit, bad healthy behavior and bad nutrition intake. Primary health center is expected to provide information by using media such as film, slide or print media to change habits, behavior and nutrition community.